Vitamin D supplementation in athletes - Larson-Meyer, E. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
It is well recognized that vitamin D is necessary for optimal bone health. Emerging evidence is finding that vitamin D deficiency can have a profound effect on immunity, inflammation and muscle function. Studies in athletes have found that vitamin D status varies among different populations and is dependent on skin color, early- or late-day training, indoor training and geographic location. Although dietary assessment studies have found that athletes worldwide do not meet the dietary intake recommendations for vitamin D, the most probable reason for poor status is inadequate synthesis due to lack of sun exposure. Studies in athletic populations suggest that maintaining adequate vitamin D status may reduce stress fractures, total body inflammation, common infectious illnesses, and impaired muscle function, and may also aid in recovery from injury. Given that compromised vitamin D status can potentially impact an athlete's overall health and training efficiency, vitamin D status should be routinely assessed so that athletes can be coached to maintain serum 25(OH)D concentration of >=30 and preferably >=40 ng/ml. Recommendations will be dependent on the athlete's current 25(OH)D concentration, but can include regular safe sun exposure and/or dietary supplementation combined with increased vitamin D intake.